2015
DOI: 10.1055/s-0034-1396434
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopy for Intracranial Arachnoid Cysts in Infants: Therapeutic Considerations

Abstract: Background?The use of the endoscope for various cranial procedures is gradually expanding. Intracranial cystic lesions in the brain are one of the most attractive targets for this minimally invasive procedure, thus avoiding conventional craniotomy. These cystic lesions in the brain, namely arachnoid cysts, are congenital. Surgical treatment depends on clinical presentation, location, and age. Patients?A total of 13 patients? Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Novel idea of endoscopic transaqueductal cysto-ventriculostomy has shifted the difficulty in approach towards an easy, less laborious procedure; video neuroendoscopy, more precise adjunct causes minimal damage to the surrounding structures and reduces associated complications. Success of neuroendoscopy for ACs in infants, 8 has demonstrated the practicality in younger patients, which is proven in the 20 day old neonate in our series.…”
Section: Discussionsupporting
confidence: 56%
“…Novel idea of endoscopic transaqueductal cysto-ventriculostomy has shifted the difficulty in approach towards an easy, less laborious procedure; video neuroendoscopy, more precise adjunct causes minimal damage to the surrounding structures and reduces associated complications. Success of neuroendoscopy for ACs in infants, 8 has demonstrated the practicality in younger patients, which is proven in the 20 day old neonate in our series.…”
Section: Discussionsupporting
confidence: 56%
“…Fahad et al reported a case that presented with precocious true puberty. The neurological deficit also can arise from the compression of adjacent structures [10,11]. The exact pathogenesis of subdural hematoma has not been detected so far.…”
Section: Discussionmentioning
confidence: 99%